2006
DOI: 10.1086/498563
|View full text |Cite
|
Sign up to set email alerts
|

A Unified Near‐Infrared Spectral Classification Scheme for T Dwarfs

Abstract: A revised near infrared classification scheme for T dwarfs is presented, based on and superseding prior schemes developed by Burgasser et al. and Geballe et al., and defined following the precepts of the MK Process. Drawing from two large spectroscopic libraries of T dwarfs identified largely in the Sloan Digital Sky Survey and the Two Micron All Sky Survey, nine primary spectral standards and five alternate standards spanning spectral types T0 to T8 are identified that match criteria of spectral character, br… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
767
2
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 462 publications
(790 citation statements)
references
References 116 publications
19
767
2
2
Order By: Relevance
“…The individual indices and the derived spectral types are shown in Table 2. We also compared visually with the standards of Burgasser et al (2006), finding a best fit of T3 [note the T3 standard of Burgasser et al (2006)] was found to be a binary by Liu, Dupuy & Leggett (2010), see later discussion on the comparison with the newer standard). As this compares well with the spectral types derived from the indices, we adopt this as our final spectral type.…”
Section: Properties Of 2mass J0213+3648 Cmentioning
confidence: 99%
See 3 more Smart Citations
“…The individual indices and the derived spectral types are shown in Table 2. We also compared visually with the standards of Burgasser et al (2006), finding a best fit of T3 [note the T3 standard of Burgasser et al (2006)] was found to be a binary by Liu, Dupuy & Leggett (2010), see later discussion on the comparison with the newer standard). As this compares well with the spectral types derived from the indices, we adopt this as our final spectral type.…”
Section: Properties Of 2mass J0213+3648 Cmentioning
confidence: 99%
“…Fig. 9 also shows a comparison with the young (∼100 Myr) T3 GU Psc b (Naud et al 2014), the young (∼300 Myr) T2.5 HN Peg B (Luhman et al 2007), the original T3 standard (2MASS J120956.13−100400.8, Burgasser et al 2006), and the alternative T3 standard (SDSS J120602.51+281328.7) suggested by Liu et al (2010) after 2MASS J120956.13−100400.8 was found to be a binary. We note that 2MASS J0213+3648 C has a narrower J band peak and deeper J-band water absorption than SDSS J120602.51+281328.7 but matches both HN Peg B and 2MASS J120956.13−100400.8 well in this regime, the H and K bands the spectrum are a better fit to SDSS J120602.51+281328.7.…”
Section: Properties Of 2mass J0213+3648 Cmentioning
confidence: 99%
See 2 more Smart Citations
“…Using the tabulated coefficients of Table 14 in Dupuy & Liu (2012) and the 2MASS and WISE Table 2. Main spectral indexes for T dwarfs as given in Burgasser et al (2006) Object…”
Section: Spectral Typingmentioning
confidence: 99%